Pilihan Bahasa pada Konten Youtube Noona Rosa: Kajian Sosiolinguistik - Leylil Nikmatur Rofiah; Arinda Lintang Ayu Sekar; Yudha Dwi Purwanti; Ayunda Riska Puspita (Asosiasi Periset Bahasa Sastra Indonesia, 2025)
This study aims to analyze the phenomenon of code-switching and code-mixing in YouTube content by Noona Rosa as a linguistic practice in a multilingual digital context. Using a descriptive qualitative approach, data were collected from several of Noona Rosa's uploaded videos and analyzed in terms of form, function, and influencing factors in the use of Indonesian and Korean code variation. The findings reveal that code-switching is employed to express emotions, reinforce cultural identity, and build rapport with bilingual audiences. Meanwhile, code-mixing commonly appears in the insertion of Korean cultural terms into Indonesian sentence structures, serving as a communicative strategy of identity and cultural meaning preservation. The influencing factors include social context, speaker identity, discussion topics, and emotional expression. These findings contribute significantly to sociolinguistic studies and highlight how digital media serves as a platform for multicultural identity expression.